2011
DOI: 10.1186/1743-422x-8-65
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a non-pathogenic H5N1 influenza virus isolated from a migratory duck flying from Siberia in Hokkaido, Japan, in October 2009

Abstract: BackgroundInfection with H5N1 highly pathogenic avian influenza viruses (HPAIVs) of domestic poultry and wild birds has spread to more than 60 countries in Eurasia and Africa. It is concerned that HPAIVs may be perpetuated in the lakes in Siberia where migratory water birds nest in summer. To monitor whether HPAIVs circulate in migratory water birds, intensive surveillance of avian influenza has been performed in Mongolia and Japan in autumn each year. Until 2008, there had not been any H5N1 viruses isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…The pre-and post-serum HI titers of #05 against non-pathogenic H5 virus, A/tundra swan/Shimane/3211A001/2011 (H5N2), were 16HI and 8HI, respectively (data not shown). It was formerly reported that there were some differences in antigenicity of H5 HAs between HPAIV and non-pathogenic viruses [12,14,22]. Therefore, #05 was thought to be previously exposed to non-pathogenic H5 virus.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-and post-serum HI titers of #05 against non-pathogenic H5 virus, A/tundra swan/Shimane/3211A001/2011 (H5N2), were 16HI and 8HI, respectively (data not shown). It was formerly reported that there were some differences in antigenicity of H5 HAs between HPAIV and non-pathogenic viruses [12,14,22]. Therefore, #05 was thought to be previously exposed to non-pathogenic H5 virus.…”
Section: Discussionmentioning
confidence: 99%
“…B. swan, black swan; Ck, chicken; HK, Hong Kong; Hok, Hokkaido; Mal, mallard; Pf, peregrine falcon; Ws, whooper swan. †Low pathogenic avian influenza viruses isolated from mallard ( 15 ) and chicken in Japan.…”
Section: The Studymentioning
confidence: 99%
“…The introduced H5N1 viruses represented three different subgroups indicating at least three separate introduction events and were closely related to virus isolates from China, Mongolia, Russia, Romania and Bulgaria (2009 – 2010) (Kajihara et al, 2011; Sakoda et al, 2012; Marinova-Petkova et al, 2012). Closely related clade 2.3.2.1 H5N1 viruses were detected in South Korea in wild birds (including various duck species, whooper swan, white-fronted goose, and predators) and during domestic poultry outbreaks (chicken, quail, turkey, duck) from December 2010 until spring 2011 (Kim et al, 2012; Kwon et al, 2011; Sakoda et al, 2010; Yamamoto et al, 2011). Throughout Japan several outbreaks of HPAI H5N1 occurred in wild birds (migratory duck, swan, grebe species; predators) and poultry (chicken) farms from late 2010 until March 2011 (Sakoda et al, 2012).…”
Section: Hpai H5n1 In Migratory Waterfowl and Other Wild Birds In mentioning
confidence: 99%